Reduction of nicotinamide adenine dinucleotide by pyruvate:lipoate oxidoreductase in anaerobic, dark-grown Rhodospirillum rubrum mutant C. - Gorrell, T E (1978)
Cell extracts from fermentatively grown Rhodospirillum rubrum reduced about 80 nmol of nicotinamide adenine dinucleotide (NAD) per mg of protein per min under anaerobic conditions with sodium pyruvate. The reaction was specific for pyruvate and NAD; NAD phosphate was not reduced. Results indicated that pyruvate-linked NAD reduction occurred via pyruvate:lipoate oxidoreductase. The reaction required catalytic amounts of both coenzyme A and thiamine pyrophosphate. Addition of sodium arsenite inhibited enzyme activity by 90%. Pyruvate:lipoate oxidoreductase was the only system detected in anaerobic, dark-grown R. rubrum cell extracts which operated to produce reduced NAD. The low activity of the enzyme system suggested that it was not quantitatively important in ATP formation.